2015
DOI: 10.1186/s12916-014-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to cigarette chemicals induces sex-specific disruption of one-carbon metabolism and DNA methylation in the human fetal liver

Abstract: BackgroundMaternal smoking is one of the most important modifiable risk factors for low birthweight, which is strongly associated with increased cardiometabolic disease risk in adulthood. Maternal smoking reduces the levels of the methyl donor vitamin B12 and is associated with altered DNA methylation at birth. Altered DNA methylation may be an important mechanism underlying increased disease susceptibility; however, the extent to which this can be induced in the developing fetus is unknown.MethodsIn this retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…An effect of maternal smoking on IGF2 expression in placenta would not be surprising since we have recently shown that maternal smoking reduces IGF2 expression in human fetal liver. 37 Maternally expressed genes including CDKN1C act to restrict fetal and placental growth, 38 and our data showing decreasing CDKN1C expression with increased birth weight are consistent with this and with a previous study reporting increased expression in association with SGA. 10 Maternal smoking had no effect on CDKN1C expression, suggesting that any effects of smoke exposure are gene-specific, again consistent with our previous data in human fetal liver.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…An effect of maternal smoking on IGF2 expression in placenta would not be surprising since we have recently shown that maternal smoking reduces IGF2 expression in human fetal liver. 37 Maternally expressed genes including CDKN1C act to restrict fetal and placental growth, 38 and our data showing decreasing CDKN1C expression with increased birth weight are consistent with this and with a previous study reporting increased expression in association with SGA. 10 Maternal smoking had no effect on CDKN1C expression, suggesting that any effects of smoke exposure are gene-specific, again consistent with our previous data in human fetal liver.…”
Section: Discussionsupporting
confidence: 81%
“…10 Maternal smoking had no effect on CDKN1C expression, suggesting that any effects of smoke exposure are gene-specific, again consistent with our previous data in human fetal liver. 37 5mC enrichment at IGF2 DMR0 and KvDMR was positively related to birth weight SD score. However the consequences of this are unclear, since there was no correlation between DNA methylation at these regions and IGF2 and CDKN1C mRNA levels.…”
Section: Discussionmentioning
confidence: 94%
“…For example, placentas derived from pregnancies of males and females display variation in the abundance and type of glucocorticoid transporter proteins, the expression of hormones and the production of immune-related proteins including cytokines [12,[19][20][21]. In addition, sex-based differences in response to prenatal stressors have been observed at the levels of the placental proteome, transcriptome and epigenome [3,7,14,20,[22][23][24][25][26][27]. Thus, the sexually dimorphic nature of the placenta could influence variation in toxicant transport and accumulation, hormone levels and immune future science group Research Article Martin, Smeester, Bommarito et al response experienced by the fetus.…”
mentioning
confidence: 99%
“…The reason why there 410 is a gender difference is still unclear and how the C1 metabolism of the fetus is 411 influenced when the mother smokes has been discussed elsewhere. 11 The data also 412 …”
mentioning
confidence: 96%
“…Cbl concentrations above the detection limits. The first results of the study has been 398 published partly by Drake et al 11 with regards to lifestyle influence on the Cbl 399 concentration in the fetal livers without describing the analytical method in detail. 400…”
mentioning
confidence: 99%